(untitled) (Південний архів (історичні науки), 2023)
In soviet society, the government tried to convey its own messages through visual content. It was used in various fields, including school education. The purpose of the article is to clarify the main thematic and content directions of the posters, which were related to school life in the Ukrainian SSR in the second half of the 1940s–1980s. The following methods were used to achieve it: historical-chronological, descriptive, comparative, diachronic. The first made it possible to analyze this topic in a chronological dimension, demonstrating the changes that took place. The second came in handy during the initial interpretation of the source. The comparative method made it possible to trace the dynamics of poster development in the specified period. Diachronic provided an opportunity to study social processes that are inherent in Soviet society and were reflected in school life. The results. Posters are designed to form a builder of society, which was characterized by certain features. The poster informed, urged, persuaded, forbade or permitted a certain activity. It was diverse in terms of subject matter, addressee, genre, periodization, authorship, and geography. The poster is aimed at the implementation of the policy of the Soviet government in the school of the Ukrainian SSR. He called for participation in adult life through work, focus on «Soviet heroes», dedication to education and future profession for a better life. In the post-war years, the topic was aimed at rebuilding the national economy and everyone’s role in it. The subsequent trend was accompanied by «catching up and overtaking the West», participation in the experiments of the Soviet government, and in this context the use of child labor in collecting scrap metal, medicinal herbs, cultivating fields, gardens, and caring for animals. The school was used as a powerful resource of influence on the public, which had a powerful material and human potential. They had certain slogans or whole precepts, depending on the audience to which their action was directed: from elementary school students, who were taught the rules of writing, to high school students who are already ready to realize their social mission. On the posters, pupils and teachers were depicted as active, smiling, serious, pensive or dreamy. Conclusions. In general, the school was positively portrayed on posters and had an impact on public opinion. It remained a mechanism for implementing the plans of the Soviet government in society.